2002
DOI: 10.1099/00221287-148-6-1795
|View full text |Cite
|
Sign up to set email alerts
|

A 5′ stem–loop and ribosome binding but not translation are important for the stability of Bacillus subtilis aprE leader mRNA

Abstract: The Bacillus subtilis aprE leader is a determinant of extreme mRNA stability.The authors examined what properties of the aprE leader confer stability on an mRNA. The secondary structure of the aprE leader mRNA was analysed in vitro and in vivo, and mutations were introduced into different domains of an aprE leader-lacZ fusion. The half-lives of the corresponding transcripts were determined and β-galactosidase activities were measured. Removal of a stem-loop structure at the 5' end or diminishing the strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 51 publications
8
74
0
Order By: Relevance
“…For example, several previous studies in Escherichia coli and Bacillus subtilis have shown that for particular model transcripts, increased ribosome binding or occupancy may enhance mRNA stability (36)(37)(38)(39)(40)(41)(42). Such studies have been hard to interpret due to the complex interactions between the ribosome, RNA degradation machinery, and transcript.…”
Section: Resultsmentioning
confidence: 99%
“…For example, several previous studies in Escherichia coli and Bacillus subtilis have shown that for particular model transcripts, increased ribosome binding or occupancy may enhance mRNA stability (36)(37)(38)(39)(40)(41)(42). Such studies have been hard to interpret due to the complex interactions between the ribosome, RNA degradation machinery, and transcript.…”
Section: Resultsmentioning
confidence: 99%
“…For example, experiments in both E. coli and B. subtilis have shown that a variety of mRNAs can be significantly destabilized by mutations in the Shine-Dalgarno element that interfere with ribosome binding by markedly reducing its complementarity to 16S rRNA (Wagner et al 1994;Arnold et al 1998;Jürgen et al 1998;Hambraeus et al 2002;Sharp and Bechhofer 2003). In E. coli, the accelerated decay of such translationally impaired mRNAs is generally mediated by RNase E (Jain and Kleckner 1993;Arnold et al 1998).…”
Section: Ribosome-binding Site Occupancymentioning
confidence: 99%
“…This finding suggests that the proximity of the PTC to the 5Ј-most initiation codon may in some cases be more important for rapid decay than the unmasking of potential cleavage sites downstream of the PTC. Furthermore, some transcripts (e.g., B. subtilis aprE, Rhodobacter capsulatus pufBA) are not destabilized by PTCs, presumably because other characteristics of these mRNAs or their host organisms make them resistant to ribonuclease attack under these circumstances (Klug and Cohen 1991;Hambraeus et al 2002;Sharp and Bechhofer 2003).…”
Section: Premature Translation Terminationmentioning
confidence: 99%
See 2 more Smart Citations